Lightweight fiber composite materials and their applications

By pretreating and modifying wood waste, forming urethane bonds and urea, enhancing the hydrophobicity and aryl structure of the fibers, the problem of poor compatibility between plant fibers and polymers is solved, and the mechanical properties of composite materials are significantly improved and thermal deformation temperature, reducing costs and pollution.

CN118684978BActive Publication Date: 2025-01-03HUAIAN JINLIDA PACKAGE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411192519.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-03
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the interface compatibility and thermoplasticity of plant fibers and polymers, resulting in poor thermoplasticity of fibers and affecting the processing and forming of materials and mechanical properties.

Method used

By pretreating wood waste, removing moisture and components, activate hydroxyl groups on cellulose, and reacting with dodecylbenzene-2,4-diisocyanate to form urethane bonds and urea, enhancing the hydrophobicity and aryl structure of the fibers , improve the compatibility of fibers and polymers.

Benefits of technology

The compatibility of fibers with polymers and the mechanical properties of composite materials are significantly improved, cost and pollution are reduced, while the hydrophobicity and thermal deformation temperature of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer compound compositions, and specifically discloses a lightweight fiber composite material and its application. The composite material is prepared by pre-treating and modifying wood waste fibers and then hot-pressing and cold-pressing them with polymers. The present invention also provides a preparation method and application thereof. Compared with the prior art, the fiber composite material prepared by the present invention has the advantages of light weight, good comprehensive performance, and green environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer compound compositions, and in particular to a lightweight fiber composite material and application thereof. Background Art

[0002] Packaging and pallets play an important role in logistics and transportation, and wooden packaging or plastic products account for a large proportion of them. However, solid wood products are bulky and not environmentally friendly, and plastic packaging is expensive and brittle. The wood-plastic composite material obtained by combining wood or fiber with plastic can solve the above problems at the same time. Plant fibers themselves have a large number of hydroxyl groups with strong polarity. These hydroxyl groups have poor compatibility with non-polar resin matrices and are prone to produce pores at the interface, which greatly reduces the ability to transfer loads and is prone to brittle fracture at stress concentration points. Therefore, it is necessary to pretreat the plant fibers to improve the interface compatibility between the two phases.

[0003] Chinese patent 201810692562.5 discloses a preparation method of a cross-linked modified straw fiber / PP wood-plastic composite material and the resulting product, the steps are: using straw skin as raw material, using chitosan and KH560 to modify the straw, and then mixing the modified straw fiber with PP, lubricant and antioxidant evenly, extruding and molding, to obtain the product. The invention overcomes the shortcomings of straw fiber's easy self-aggregation and poor compatibility with the polymer matrix by cross-linking pretreatment of the straw fiber, improves the compatibility of the straw fiber and the PP matrix, and improves the interface performance of the straw fiber and PP, so that the addition amount of straw fiber can reach 40%, greatly improving the recycling rate of straw fiber, and finding a new path for the application of crop straw fiber in wood-plastic composite materials.

[0004] Chinese patent 202010305027.7 discloses a dynamically covalently cross-linked cellulose-based bioplastic, a wood-plastic composite material and a preparation method thereof. The method reconstructs the hydrogen-bonded network between cellulose molecular chains into a dynamic covalently linked network to prepare a heat-processable, high-strength, high-modulus, degradable and recyclable cellulose-based bioplastic. Compared with most existing hydrogen-bonded cellulose-based materials, the cellulose-based bioplastic prepared by the invention is cross-linked by dynamic covalent bonds, which makes the cellulose-based plastic have excellent reprocessing, thermal processing and degradability. The new wood-plastic composite material prepared by it and biomass has higher tensile strength and Young's modulus because the interfacial compatibility between the two phases can be improved through hydrogen bond interaction.

[0005] At present, the existing technology often improves the compatibility of fibers through the following aspects: pre-treating plant fibers, reducing the polarity of raw materials or removing extracts that are unfavorable to the interface, or adding interface modifiers such as coupling agents to modify the fibers. However, this modification method cannot solve the problem of poor thermoplasticity of fibers, and the thermoplasticity of wood-plastic materials will affect the final processing and molding. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a lightweight fiber composite material and application thereof.

[0007] The mechanical parameters of most plant fibers are lower than those of synthetic fibers, but the advantages of plant fibers themselves, such as diversity, affinity and low price, are very suitable as reinforcements for plastics. Using plant fibers to reinforce plastics can not only improve strength and hardness, but also reduce shrinkage, increase heat deformation temperature and impact strength, etc. At the same time, under the condition of contact with microorganisms, it is easier to degrade, and is currently a more ideal reinforcement. Because of the presence of hydroxyl groups and hydrogen bonds in the structure of plant fibers, it has strong polarity and water absorption. In the present invention, firstly, by pre-treating wood waste, on the one hand, the moisture in the fiber can be removed, and on the other hand, components such as hemicellulose, pectin and lignin are removed, most of the cellulose is retained, the hygroscopicity is reduced, and the hydroxyl groups on the cellulose are activated at the same time, which prepares the conditions for the next step of modification. After pre-treatment, it is mixed with dodecylbenzene-2,4-diisocyanate, and a large number of hydroxyl groups on the fiber are coupled with isocyanate to produce urethane bonds, which provide strength for the composite material prepared later. In addition, isocyanate can also react with the moisture remaining on the fiber surface to form urea, which will then react with the hydroxyl groups in the cellulose. Due to this reaction and the hydrophobic alkyl chains grafted on the surface, the hydrophobicity of the fiber is enhanced and the interfacial compatibility with the polymer is also better. When the modified fiber is composited with polystyrene, since both the matrix and the modified fiber structure contain aromatic groups, the electron cloud formed by the delocalized π electrons of the aromatic group will interact strongly, resulting in better compatibility between the fiber and the polymer. At the same time, the aromatic rigid groups grafted on the fiber surface and the formed urethane bonds can significantly improve the mechanical properties of the composite material.

[0008] To achieve the above object, the present invention provides a method for preparing a lightweight fiber composite material, comprising the following steps:

[0009] The modified fiber, polystyrene and lubricant are mixed in a mass ratio of 20-40:60-80:1-10, dispersed evenly and added into a hot pressing mold for hot pressing. After the hot pressing is completed, the mold is removed and cold pressing is performed to obtain the product.

[0010] The method for preparing the modified fiber comprises the following steps:

[0011] X1: Crush and sieve the wood waste fibers, add them into a sodium hydroxide aqueous solution and treat for 4-6 hours, filter and wash the fiber surface with water, and use them in the next step after drying;

[0012] X2: Add the fiber treated in the previous step into acetone, add dodecylbenzene-2,4-diisocyanate, heat to 60-80°C under a nitrogen atmosphere and stir for 8-10 hours. After stirring, filter, wash the residue three times and dry to obtain the modified fiber.

[0013] Furthermore, the material-liquid ratio of the wood waste fiber to the sodium hydroxide aqueous solution is 1:5~10g / mL.

[0014] Furthermore, the sodium hydroxide aqueous solution is 1 mol / L.

[0015] Furthermore, the material-liquid ratio of the treated fiber to acetone is 1:10-20 g / mL; the mass of dodecylbenzene-2,4-diisocyanate is 10-20 wt % of the treated fiber.

[0016] Furthermore, the lubricant is polyethylene wax.

[0017] Furthermore, the temperature of the hot pressing is 160-190°C.

[0018] Furthermore, the hot pressing pressure is 5-10 MPa.

[0019] Furthermore, the hot pressing time is 5 to 10 minutes.

[0020] Furthermore, the cold pressing pressure is 2-5 MPa.

[0021] Furthermore, the cold pressing time is 3 to 8 minutes.

[0022] Preferably, the method for preparing the modified fiber comprises the following steps:

[0023] X1: The wood waste fiber was crushed and sieved, and then added into 1 mol / L sodium hydroxide aqueous solution for 4-6 hours, with the solid-liquid ratio of 1:5-10 g / mL. After filtering, the fiber surface was washed with water, and then dried for the next step;

[0024] X2: Add the treated fiber in the previous step into acetone with a solid-liquid ratio of 1:10~20g / mL, add dodecylbenzene-2,4-diisocyanate with a mass of 10~20wt% of the treated fiber, heat to 60~80℃ under nitrogen atmosphere and stir for 8~10h. Filter after stirring, wash the residue 3 times and dry to obtain modified fiber.

[0025] Beneficial effects of the present invention:

[0026] 1. Compared with the prior art, the present invention can not only achieve lightweight, but also reduce costs and pollution by compounding modified fibers with polymers.

[0027] 2. The present invention processes and modifies the fibers, which not only improves the compatibility with the polymer, but also improves the hydrophobicity and mechanical strength, thereby significantly improving the mechanical properties of the composite material. DETAILED DESCRIPTION

[0028] Dodecylbenzene-2,4-diisocyanate, CAS No.: 93859-04-2.

[0029] Polyethylene wax, model: SX-115B, Yanshan Petrochemical.

[0030] Polystyrene, model: GPPS-158K, Yuyao Chihong Plastics.

[0031] Example 1

[0032] A method for preparing a lightweight fiber composite material comprises the following steps:

[0033] The modified fiber, polystyrene and polyethylene wax were mixed in a mass ratio of 30:70:5, dispersed evenly and added into a hot pressing mold, and hot pressed for 10 minutes at 8MPa and 160°C. After the hot pressing, the mold was removed and cold pressed for 5 minutes at 4MPa.

[0034] The method for preparing the modified fiber comprises the following steps:

[0035] X1: The wood waste fiber was crushed through a 100 mesh sieve, added to a 1 mol / L sodium hydroxide aqueous solution and treated for 5 h, with a solid-liquid ratio of 1:10 g / mL. After filtering, the fiber surface was washed with water and dried for the next step;

[0036] X2: Add the treated fiber in the previous step into acetone with a solid-liquid ratio of 1:15 g / mL, add dodecylbenzene-2,4-diisocyanate with a mass of 15 wt% of the treated fiber, heat to 70 °C under a nitrogen atmosphere and stir for 10 h. After stirring, filter and wash the residue 3 times and dry to obtain the modified fiber.

[0037] Example 2

[0038] The same as Example 1, the only difference is that the mass of dodecylbenzene-2,4-diisocyanate is 10wt% of the treated fiber.

[0039] Example 3

[0040] The same as Example 1, the only difference is that the mass of dodecylbenzene-2,4-diisocyanate is 20wt% of the treated fiber.

[0041] Example 4

[0042] The same as Example 1, the only difference is that the mass ratio of modified fiber, polystyrene and lubricant is 40:70:5.

[0043] Comparative Example 1

[0044] A method for preparing a lightweight fiber composite material comprises the following steps:

[0045] The modified fiber, polystyrene and polyethylene wax were mixed in a mass ratio of 30:70:5, dispersed evenly and added into a hot pressing mold, and hot pressed for 10 minutes at 8MPa and 160°C. After the hot pressing, the mold was removed and cold pressed for 5 minutes at 4MPa.

[0046] The method for preparing the modified fiber comprises the following steps:

[0047] X1: The wood waste fiber was crushed through a 100 mesh sieve, added to a 1 mol / L sodium hydroxide aqueous solution and treated for 5 h, with a solid-liquid ratio of 1:10 g / mL. After filtering, the fiber surface was washed with water and dried for the next step;

[0048] X2: Add the treated fiber in the previous step into acetone with a solid-liquid ratio of 1:15 g / mL, add dodecyl isocyanate with a mass of 15 wt% of the treated fiber, heat to 70 °C under a nitrogen atmosphere and stir for 10 h. After stirring, filter and wash the residue 3 times and dry to obtain the modified fiber.

[0049] Comparative Example 2

[0050] A method for preparing a lightweight fiber composite material comprises the following steps:

[0051] The modified fiber, polystyrene and polyethylene wax were mixed in a mass ratio of 30:70:5, dispersed evenly and added into a hot pressing mold, and hot pressed for 10 minutes at 8MPa and 160°C. After the hot pressing, the mold was removed and cold pressed for 5 minutes at 4MPa.

[0052] The method for preparing the modified fiber comprises the following steps:

[0053] X1: The wood waste fiber was crushed through a 100 mesh sieve, added to a 1 mol / L sodium hydroxide aqueous solution and treated for 5 h, with a solid-liquid ratio of 1:10 g / mL. After filtering, the fiber surface was washed with water and dried for the next step;

[0054] X2: Add the treated fiber in the previous step into acetone with a solid-liquid ratio of 1:15 g / mL, add o-toluene isocyanate with a mass of 15 wt% of the treated fiber, heat to 70 °C under a nitrogen atmosphere and stir for 10 h. After stirring, filter and wash the residue 3 times and dry to obtain the modified fiber.

[0055] Comparative Example 3

[0056] A method for preparing a lightweight fiber composite material comprises the following steps:

[0057] The modified fiber, polystyrene and polyethylene wax were mixed in a mass ratio of 30:70:5, dispersed evenly and added into a hot pressing mold, and hot pressed for 10 minutes at 8MPa and 160°C. After the hot pressing, the mold was removed and cold pressed for 5 minutes at 4MPa.

[0058] The method for preparing the modified fiber comprises the following steps:

[0059] The wood waste fiber was crushed through a 100-mesh sieve, added into a 1 mol / L sodium hydroxide aqueous solution and treated for 5 h, with a solid-liquid ratio of 1:10 g / mL. After filtering, the fiber surface was washed with water, and the modified fiber was obtained after drying.

[0060] Test Example 1

[0061] The prepared lightweight fiber composite material was tested for performance according to GB / T 29418-2012 "Test of Physical and Mechanical Properties of Plastic Wood Composite Materials", and the three-point bending test parameters were determined. The prepared composite material was processed into a sample with a size of 60mm×10mm×2mm according to the requirements. The test speed was 1mm / min, and the experimental data was recorded. The experimental results are the arithmetic mean of 3 parallel sample tests.

[0062] Table 1 Mechanical properties test of lightweight fiber composite materials

[0063]

[0064] By comparing Reference Example 3 with Reference Examples 1-2 and Example 1, it can be found that modifying the fiber can significantly improve the mechanical properties of the composite material. This may be because the fiber, as a material with strong polarity, has a large number of active hydroxyl groups on the surface after treatment, and has poor compatibility with organic polymers. Therefore, the compatibility of the two phases is poor when it is not modified, and the best reinforcement effect of the fiber cannot be exerted. In Example 1, by treating and modifying the fiber, a hydrophobic alkyl chain is grafted on its surface, which not only improves the defect of large surface polarity of the fiber, but also mixes it with dodecylbenzene-2,4-diisocyanate after pretreatment, and a large number of hydroxyl groups on the fiber are coupled with isocyanate to produce urethane bonds, providing strength for the composite material prepared later. In addition, isocyanate can also react with the moisture remaining on the fiber surface to form urea, which will then react with the hydroxyl groups in cellulose. Due to this reaction and the hydrophobic alkyl chains grafted on the surface, the hydrophobicity of the fiber is enhanced, and the interfacial compatibility with the polymer is also better. When the modified fiber is compounded with polystyrene, since both the matrix and the modified fiber structure contain aromatic groups, the electron cloud formed by the aromatic delocalized π electrons will interact strongly, resulting in better compatibility between the fiber and the polymer. At the same time, the aromatic rigid groups grafted on the fiber surface and the formed urethane bonds can significantly improve the mechanical properties of the composite material. In Control Example 1, the dodecyl isocyanate only grafted hydrophobic alkyl chains on the fiber surface, and the compatibility was improved. In Control Example 2, the mechanical properties were enhanced by the grafted aromatic rigid groups. In Control Example 3, the treated fiber was not further treated, so the compatibility was poor, and the mechanical properties were the worst.

[0065] Test Example 2

[0066] According to the test method of GB / T 17657-2022 "Test Methods for Physical and Chemical Properties of Artificial Boards and Faced Artificial Boards", three specimens of 20mm×20mm×2mm are sawed from different parts of each sample of the prepared lightweight fiber composite material, and the specimens are placed in an environment with room temperature and relative humidity maintained at (65±5)% until the mass does not change and then weighed; then the specimens of different groups are immersed in a beaker in groups, and the specimens are immersed vertically in the water surface, and the relative distance between the specimens is maintained so that the specimens do not affect each other. After the first immersion for 24 hours, the specimens are slowly taken out, the water on the surface of the specimens is wiped off, and they are weighed immediately, which is the 24-hour water absorption rate. The water absorption rate is the ratio of the difference in mass of the specimen before and after immersion to the mass of the specimen after drying.

[0067] Table 2 Water absorption test of lightweight fiber composite materials

[0068]

[0069] For wood-plastic composite materials, water absorption may cause the material to become moldy, weaken its strength, and deform its morphology. From the comparison between the control example and the embodiment, it can be found that the water absorption rate of Example 1 is the lowest. This may be because the hydrophobic alkyl chain is grafted on its surface by treating and modifying the fiber, and the isocyanate can also react with the residual moisture on the fiber surface to form urea, which will then react with the hydroxyl groups in the cellulose. Due to this reaction and the hydrophobic alkyl chain grafted on the surface, the hydrophobicity of the fiber is enhanced, so that the composite material is not easy to absorb water. In Control Example 2, since the modified o-toluene isocyanate does not have a hydrophobic alkyl chain, the water absorption rate is relatively high. In Control Example 3, the treated fiber is not further treated. There are a large number of hydroxyl groups on the cellulose surface. Although polystyrene itself is hydrophobic, the addition of cellulose still affects its water absorption.

[0070] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a lightweight fiber composite material, characterized in that: The steps include: The modified fiber, polystyrene and lubricant are mixed in a mass ratio of 20-40:60-80:1-10, dispersed evenly and added into a hot pressing mold for hot pressing, after the hot pressing is completed, the mold is removed and cold pressing is performed; The method for preparing the modified fiber comprises the following steps: X1: The wood waste fiber was crushed and sieved, and then added into 1 mol / L sodium hydroxide aqueous solution for 4-6 hours, with the solid-liquid ratio of 1:5-10 g / mL. After filtering, the fiber surface was washed with water, and then dried for the next step; X2: Add the treated fiber in the previous step into acetone with a solid-liquid ratio of 1:10~20g / mL, add dodecylbenzene-2,4-diisocyanate with a mass of 10~20wt% of the treated fiber, heat to 60~80℃ under nitrogen atmosphere and stir for 8~10h. Filter after stirring, wash the residue 3 times and dry to obtain modified fiber.

2. The method for preparing a lightweight fiber composite material according to claim 1, characterized in that: The lubricant is polyethylene wax.

3. The method for preparing a lightweight fiber composite material according to claim 1, characterized in that: The temperature of the hot pressing is 160-190° C., the pressure of the hot pressing is 5-10 MPa, and the time of the hot pressing is 5-10 min.

4. The method for preparing a lightweight fiber composite material according to claim 1, characterized in that: The cold pressing pressure is 2-5 MPa, and the cold pressing time is 3-8 min.

5. A lightweight fiber composite material, characterized in that: Prepared by the method according to any one of claims 1 to 4.

6. Use of the lightweight fiber composite material as claimed in claim 5 in a pallet or a packaging box.